EFEKTIVITAS PROGRAMA “LAPORO REK” RADIO SUARA KOTA SEBAGAI MEDIA KOMUNIKASI PARTISIPATORIS MASYARAKAT DALAM PEMBANGUNAN DI KOTA PROBOLINGGO - Mailinda Komariyah; Totok Wahyu Abadi (Universitas Muhammadiyah Sidoarjo, 2015)
The purpose of this study was to determine how much effectiveness programa laporo rek suara kota radio as media communication participatory community on development in the probolinggo city. This type of research used an explanatory research with quantitative approach. Samples are taken a number of 100 respondents to the listeners of Radio Suara Probolinggo city of precision was set 5% of the population of 285 people. The results of research indicated that the data were analyzed quantitatively with the support of frequency tables were simple and data tabulation by using SPSS 17 application. The results in this research used path analysis. It showed that overall amount of influence in directly or indirectly effect on the willingness variable (X1) obtained amounted of 0.78 or 78%, opportunity variables (X2) amounted of 0.273 and ability variable (X3) amounted of 0,016. This indicated that the willingness, opportunity and ability had influenced and increased community participation in the development of mediated programa Laporo Rek.